3B.07: MID-REGIONAL PRO-ATRIAL NATRIURETIC PEPTIDE AND BLOOD PRESSURE IN ADOLESCENTS. (June 2015) - Jeppesen, J.; Goharian, T.; Gimsing, A.; Faber, J.; Goetze, J.; Andersen, L.; Grøntved, A.
Abstract : Objective: To study the relationship between blood pressure, circulating natriuretic peptide concentrations, gender, and pubertal stage in generally healthy adolescents. Design and method: Cross-sectional study of 15-year-old females and males (n = 335) from the Danish site of the European Youth Heart Study. Blood pressure was measured using a standardised protocol, sexual maturity was assessed according to Tanner's stages, and as a surrogate for atrial natriuretic peptide, we measured mid-regional pro-atrial natriuretic peptide in plasma. Results: Compared with boys, girls had lower systolic blood pressure (mean ± standard deviation: 109.6 ± 9.9 mm Hg vs. 116.9 ± 11.4 mm Hg, P < 0.0001) and higher plasma mid-regional pro-atrial natriuretic peptide concentrations (median (interquartile range): 42.1 pmol/L (31.9–50.2) vs. 36.6 pmol/L (30.6–44.9), P = 0.0046). When female adolescents were further subdivided according to Tanner's stages, there were no differences in blood pressure and plasma mid-regional pro-atrial natriuretic peptide concentrations between post-pubertal and pubertal girls (P > 0.17). In contrast after similar subdivision, post-pubertal boys had higher systolic blood pressure (mean ± standard deviation: 117.7 ± 11.7 mm Hg vs. 111.4 ± 7.9 mm Hg, P = 0.029) and lower plasma mid-regional pro-atrial natriuretic peptide concentrations (median (interquartile range): 36.2 pmol/L (30.6–43.1) vs. 46.4 pmol/L (30.3–51.1), P = 0.043) compared with pubertal boys. Conclusions: Given their higher systolic blood pressure, boys had lower than expected plasma concentrations of mid-regional pro-atrial natriuretic peptide compared with girls, and given their higher systolic blood pressure, post-pubertal boys had lower than expected plasma concentrations of mid-regional pro-atrial natriuretic peptide compared with pubertal boys. Therefore, our study adds to the growing body of evidence to suggest that in healthy individuals a lower circulating amount of atrial natriuretic peptide, resulting in diminished vasodilation and natriuresis, leads to higher blood pressure. Furthermore, our study provides further evidence to suggest that testosterone lowers circulating atrial natriuretic peptide concentrations, and thereby our study offers one possible explanation of why boys and younger men have higher blood pressure and higher risk of hypertension compared with girls and younger women.